Association of Minimally Invasive Evacuation of Intracerebral Hemorrhage With Functional Outcomes: A Systematic Review and Meta-Analysis - Andrian Dwi Rizki Setyawan; Titik Setyawan; Edy Sucipto (International Medical Journal Corp. Ltd, 2025)
Background: Spontaneous intracerebral hemorrhage (ICH) is the most lethal form of stroke, associated with profound morbidity and mortality. The role of surgical intervention has been a subject of long-standing debate, with conventional craniotomy failing to demonstrate consistent benefits over medical management in large trials. Minimally Invasive Surgery (MIS) has emerged as a promising alternative designed to mitigate iatrogenic injury while achieving hematoma evacuation. This study aims to synthesize high-quality evidence on the efficacy and safety of MIS for ICH. Methods: A systematic review and meta-analysis were conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. We performed a comprehensive search of PubMed, Google Scholar, Semanthic Scholar, Springer, Wiley Online Library for high-quality randomized controlled trials (RCTs) comparing MIS (including endoscopic surgery and stereotactic aspiration) with conventional treatment (standard medical management or craniotomy) in adult patients with spontaneous supratentorial ICH. The primary outcomes were favorable functional outcome, defined as a modified Rankin Scale (mRS) score of 0–3, and all-cause mortality at the longest available follow-up. A random-effects model was used to pool Odds Ratios (ORs) and 95% Confidence Intervals (CIs). Results: Sixteen high-quality RCTs encompassing 3,781 patients (1,923 randomized to MIS and 1,858 to conventional treatment) met the inclusion criteria. The meta-analysis revealed that MIS was significantly associated with a higher likelihood of achieving a favorable functional outcome (OR, 1.51; 95% CI, 1.25–1.82; ). Furthermore, MIS was associated with significantly lower odds of long-term mortality (OR, 0.72; 95% CI, 0.57–0.90; ) and early mortality within 30 days (OR, 0.73; 95% CI, 0.56–0.95; ). Secondary analyses demonstrated that MIS also led to significantly lower rates of postoperative infections, shorter operative times, and reduced lengths of stay in both the intensive care unit and the hospital. Rates of rebleeding were not significantly different between the groups (OR, 1.10; 95% CI, 0.55–2.19; ). Discussion: The pooled evidence strongly supports the superiority of MIS over conventional treatment for selected patients with ICH. These findings are consistent with and reinforced by recent landmark trials such as ENRICH, which provided Level 1 evidence for the benefit of an MIS approach in lobar hemorrhages. The efficacy of MIS appears contingent on achieving near-complete hematoma evacuation in a timely manner, a principle established in the MISTIE III trial. Conclusion: This meta-analysis provides robust, high-quality evidence supporting the use of MIS as a primary treatment strategy in the management of spontaneous supratentorial ICH. MIS is associated with substantial improvements in both functional independence and survival.